A simple route to develop transparent doxorubicin-loaded nanodiamonds/cellulose nanocomposite membranes as potential wound dressings. (5th June 2016) - Luo, Xiaogang; Zhang, Hao; Cao, Zhenni; Cai, Ning; Xue, Yanan; Yu, Faquan
Highlights: It presents a simple method to develop nanodiamonds/cellulose nanocomposite membranes. Nanodiamonds/cellulose nanocomposite membranes have interpenetrating porous structure. Transparent property allows daily visual inspections without dressing removal. Nanocomposite membranes were applied for controlled release of DOX. Release of DOX was pH dependence and effectively eradicated HeLa cells. Abstract: The objective of this study is to develop transparent porous nanodiamonds/cellulose nanocomposite membranes with controlled release of doxorubicin for potential applications as wound dressings, which were fabricated by tape casting method from dispersing carboxylated nanodiamonds and dissolving cellulose homogeneously in 7 wt% NaOH/12 wt% urea aqueous solution. By adjusting the carboxylated nanodiamonds content, various nanocomposite membranes were obtained. The structure and properties of these membranes have been investigated by light transmittance measurements, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), tensile tests, water loss analyses, etc. The drug loading and release was investigated using doxorubicin hydrochloride as a model drug. In vitro cytotoxicity assay of the membranes was also studied. This work presented a proof-of-concept utility of these membranes for loading and release of bioactive compounds to be employed as a candidate for wound dressing.